2020
DOI: 10.1136/bmjopen-2019-036222
|View full text |Cite
|
Sign up to set email alerts
|

Surgical trends, outcomes and disparities in minimal invasive surgery for patients with endometrial cancer in England: a retrospective cohort study

Abstract: ObjectiveTo examine surgical outcomes and trends in the implementation of minimally invasive surgery (MIS) use for endometrial cancer (EC).DesignRetrospective cohort study.SettingEnglish National Health Service hospitals 2011–2017/2018.Population35 304 patients having a hysterectomy for EC identified from Hospital Episode Statistics.MethodsUnivariate and multivariate analyses compared MIS to open hysterectomy (OH) by assessing the association between demographic, clinical and hospital characteristics by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 27 publications
2
35
1
Order By: Relevance
“…There will always be a proportion of cases that have to be performed OH due to contraindications/complications with MIS, which will inevitably attract higher costs due to their complexity, but this can be reduced to low levels. 17 The significantly higher complication/readmission rate with OH has been reported previously 8 and in this study we have shown that even in the HC groups, the complication rate was higher with OH (71.5%) as compared with RH (55.6%) and LH (61.0%). A longer recovery time may impact on patient and employment costs, with greater loss of earnings and longer return to work or contribution to society activities as compared with MIS.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…There will always be a proportion of cases that have to be performed OH due to contraindications/complications with MIS, which will inevitably attract higher costs due to their complexity, but this can be reduced to low levels. 17 The significantly higher complication/readmission rate with OH has been reported previously 8 and in this study we have shown that even in the HC groups, the complication rate was higher with OH (71.5%) as compared with RH (55.6%) and LH (61.0%). A longer recovery time may impact on patient and employment costs, with greater loss of earnings and longer return to work or contribution to society activities as compared with MIS.…”
Section: Discussionsupporting
confidence: 64%
“…As previously described, there was a significant difference in the social/ethnic characteristics of the patients undergoing MIS as compared with OH within this cohort of patients. 8 The characteristics of the RH population differed to patients undergoing LH; with a significantly higher percentage of RH patients having any comorbidity from our defined list than LH (68.2% vs 64.0%, p<0.001), more specifically the comorbidities of diabetes, hypertension and obesity all being higher proportion in RH cohort than LH cohort.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations